Percutaneous closure of an iatrogenic aorto-right atrial fistula of the sinus of Valsalva through total arm approach: a case report. Issue 1 (23rd December 2019) - Sood, Nitin; Ehrlich, Peter; Meerbach, Dorothee; Kindermann, Michael
Abstract: Background : Creation of an iatrogenic aorto-right atrial fistula is a rare but clinically relevant complication of cardiac surgery. Transfemoral percutaneous closure is an attractive alternative to surgical repair, but there are no reports about transcatheter repair using a complete arm access. Case summary : We present the case of a 44-year-old woman with heart failure (NewYork Heart Association Class III) due to a longstanding iatrogenic fistula from the non-coronary aortic cusp to the right atrium (RA) with aorta to RA shunting and severe tricuspid regurgitation (TR) caused by mitral valve replacement 15 years ago. The patient was successfully treated by percutaneous closure with an Amplatzer Vascular Plug II using complete brachial access. Following the procedure right heart chambers and TR decreased and symptoms resolved. Discussion : To the best of our knowledge this is the first report of percutaneous repair of an aorto-right atrial fistula using total arm accesses (radial artery and basilic vein). In appropriately selected patients, this approach is an attractive alternative to femoral access.